Analisis dan Perancangan Sistem Informasi Pemodelan Consultant Berbasis Digital - Muhammad Abdul Mu’ti Andriansyah; Muhammad Mahmud Mahfuz; Sastia Rahmadani Azzahra; Zatin Niqotaini (GLOBAL SCIENTS PUBLISHER, 2026)
In the continuously evolving digital era, the demand for consultation services that are fast, easily accessible, and well-integrated is increasing. Many consultation services are still conducted conventionally, making communication processes, service searches, and data management time-consuming and less efficient. This study discusses the analysis and design of a digital-based consultant information system aimed at facilitating the consultation process between users and consultants in an effective and structured manner. The system is designed to assist users in searching for consultation services, making bookings, processing payments, and providing reviews of services they have utilized. The research methodology includes problem identification, data collection through observation and literature review, as well as system analysis and design using the Unified Modeling Language (UML) approach. The system design process involves the development of several models, including use case diagrams, activity diagrams, sequence diagrams, class diagrams, and database design to support data management processes within the system. In addition, a user interface design is developed to ensure ease of use for both users and consultants. The results of this study are presented in the form of a digital-based consultation service information system design capable of supporting more effective service management processes. The proposed system is expected to improve service quality, accelerate consultation processes, simplify data management, and provide a better user experience for both users and consultants. Furthermore, the implementation of this digital system can support more structured data storage and minimize errors in information processing.